2019
DOI: 10.1186/s12876-019-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and inflammation in non-alcoholic fatty liver disease: a randomized, placebo controlled clinical trial

Abstract: Background The aim of the present study was to evaluate the effects of curcumin supplementation on inflammatory indices, and hepatic features in patients with non-alcoholic fatty liver disease (NAFLD). Methods Fifty patients with NAFLD were randomized to receive lifestyle modification advice plus either 1500 mg curcumin or the same amount of placebo for 12 weeks. Results Curcumin supplementation was associated with significant decrease in hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 28 publications
1
64
1
Order By: Relevance
“…Nevertheless, absent histological evaluation of changes following curcumin treatment strongly limits impact of the studies especially in terms of their anti-fibrotic capacity [379,380]. Moreover, a recent placebo-controlled clinical trial investigating lifestyle modification plus curcumin supplementation vs. placebo in 50 patients with NASH did not find significant advantages of curcumin in amelioration of biochemical and sonographic liver inflammation, steatosis, and fibrosis compared to lifestyle intervention alone [381]. Well-designed randomized placebo-controlled trials including histological examination are needed to define curcumin's significance in clinical practice.…”
Section: Phytodrugs With Multi-dimensional Effects On Liver Fibrosismentioning
confidence: 99%
“…Nevertheless, absent histological evaluation of changes following curcumin treatment strongly limits impact of the studies especially in terms of their anti-fibrotic capacity [379,380]. Moreover, a recent placebo-controlled clinical trial investigating lifestyle modification plus curcumin supplementation vs. placebo in 50 patients with NASH did not find significant advantages of curcumin in amelioration of biochemical and sonographic liver inflammation, steatosis, and fibrosis compared to lifestyle intervention alone [381]. Well-designed randomized placebo-controlled trials including histological examination are needed to define curcumin's significance in clinical practice.…”
Section: Phytodrugs With Multi-dimensional Effects On Liver Fibrosismentioning
confidence: 99%
“…Hyperlipidemia induces the lipid accumulation in liver, resulting in the liver dysfunction (Qi et al., 2019; Ramos et al., 2020; Saadati et al., 2019). To investigate the mechanism underlying the protection against liver dysfunction by knockout of calpain‐1, the lipid profiles in serum and liver were determined.…”
Section: Discussionmentioning
confidence: 99%
“…Panahi Y et al also observed lipid-lowering effect in their randomized controlled trial using curcuminoids (1 g/ day plus piperine 10mg/day) treatment of diabetes patients for 12 weeks (Panahi et al, 2018). Finally, a treatment with amorphous dispersion curcumin formulation (500 mg/day equivalent to 70mg curcumin) of non-alcoholic fatty liver patients for 8 weeks resulted in BMI-reduction as well as plasma Tg, LDL, and glucose levels lowering (Saadati et al, 2019). In the placebo-controlled clinical study of the effect of 1-year licorice root extract consumption on cardiovascular risk factors, beneficial results were demonstrated, namely, the significant reduction of TC and LDL levels as well as hypotensive activity (Fogelman et al, 2016).…”
Section: Effectmentioning
confidence: 94%
“…Phytoestrogens are characterized by lipid-lowering and hypotensive effects. Villa P et al in their pilot randomized trial involving ninety women in menopausal transition showed that administration of phytoestrogen substances in addition to vitamins and passionflower herbal preparation during 6 months led to TC decrease in blood plasma (Saadati et al, 2019). Eight-week of soy nut diet helped to decrease of fasting blood glucose as well as to improve blood lipids profile, significantly decreasing TC and LDL (Fogelman et al, 2016).…”
Section: Effectmentioning
confidence: 99%
See 1 more Smart Citation